DEVELOPING READING COMPREHENSION ABILITIES - Abdullah Farih (Reforma : Jurnal Pendidikan dan Pembelajaran, 2016)
Teaching reading a second or foreign language receives a special focus. Some students of foreign language give the most important goal. They get the information through reading, as like newspaper, books, article, etc. good reading text also provide good writing models. So it needs strategies in order to get the best value in the process and the final output. Some strategies are proposed by the expert, but we should select where the appropriate to teach on the students. The aim of the study is to know what the best way to teach reading comprehension students as a second or foreign language is. It is important because nowadays, there are many book sources that use English as their language. This article will discuss (1) the strategies for reading comprehension, (2) the understanding of reading comprehension and teaching reading comprehension. The finding of the study show that the way of teaching reading comprehension is different; and it must adopt the strategy of reading comprehension of the students. Keywords: reading strategy, reading comprehension